Applications of algae for environmental sustainability: Novel bioplastic formulation method from marine green alga - El Semary, Nermin; Alsuhail, Muneerah; Al Amer, Kawther; AlNaim, Abdulallah (Frontiers in Marine Science, 2022)
(1) Background. Marine algae have several economic uses including their recent use in the production of bioplastics. However, the Arabian Gulf area, despite being rich in macroscopic algae, has not been exploited in that regard . The present research aims at studying the generation of bioplastic from marine green macroscopic alga from the Eastern province, Saudi Arabia. Materials and Methods. Green macroalgal biomass was collected from Al Uquair coastal region, dried and ground until becoming fine powder. The identity of this green alga was investigated using molecular methods. Different treatments were tried but did not work. One treatment that combines both the natural plant-based plasticizer Plantago ovata with the synthetic plasticizer. Polyethylene glycol 4500 was effective in making a tensile polymer whose properties were further enhanced by adding glycerol one day after forming the blend. Different spectrometric, thermal and mechanical characterization of the blend were analyzed including FTIR spectroscopy, dynamic mechanical analyzer (DMA) for Tensile strength as well as thermogravimetric analysis (TGA) for thermal stability. Results. The combination of plant-based plasticizer with algal biomass caused the formation of a polymer with excellent tensile properties and Thermal stability. FTIR confirmed the formation of starch-based blend whose functional groups O–H, C–H, C=O, and C–O confirmed the formation of starch bioplastics. derived from both starch and cellulose in green alga and in Plantago ovata. Conclusion. The present research provides a cost-effective novel method that is mostly based on using whole algal biomass in addition natural material that are biodegradable for manufacturing of bioplastics to be used in a number of applications in addition to being bio-degradable and sustainable at the same time.